Efektivitas Booklet Dan Wondershare Video Dalam Meningkatkan Pengetahuan Dan Perilaku Jumantik-PSN Dan Angka Bebas Jentik Pada SMP Negeri Kecamatan Jekan Raya Kota Palangka Raya - Natalansyah Natalansyah (Jurnal Surya Medika (JSM), 2020)
Dengue Hemorrhagic Fever is a contagious disease and is a major public health problem in Indonesia. Palangkaraya City's DBD IR for three years has continued to increase and become 68% and CFR 2% in 2018, this is due to the community's participation in PSN activities that have not been carried out optimally. One of the strategies to optimize community participation in the prevention and control of Dengue Fever is the empowerment of students with video media and booklets in improving the behavior of Jumantik-PSN school children. The purpose of this study was to determine the differences in the use of the WonderShare video media with booklets in increasing the behavior of jumantik-PSN school children and larva free rates in SMP Negeri 9 and 16 in the area of Kayon Puskesmas, Jekan Raya District, Palangka Raya City. This study used an experimental design. Two groups of pre and posttest designs. Samples were 50 students in grade 7 & 8, each of 25 groups of video media and booklets, instruments used were WonderShare videos, booklets, questionnaires, checklist sheets. The results showed that the independent t-test - there was a difference in the increase in mean scores, Knowledge between the video group and the booklet: P = 0.041 (P <0.5)Conclusion: Video media is effective in increasing Jumantik-PSN knowledge of school children and reducing larva free rates. Suggestion: to schools and Puskesmas to innovate counseling media with WonderShare video (video via WhatsApp) in increasing Jumantik-PSN's knowledge about the prevention and prevention of DHF so as to reduce larva free rates and cases.